Clinical Characteristics of the Patients with Corona Virus Disease 2019 in Sylhet District of Bangladesh - Begum, Momtaz; Deb, Bidith Ranjan; Das, Shantanu; Chowdhury, Fahmida; Ahmed, Shabbbir; Hamid, Nasser; Moureen, Adneen (Bangladesh Journal of Infectious Diseases, 2024)
Background: Bangladesh has suffered a lot corona virus disease 2019 (COVID 19), but clinical data on COVID 19 is fewer still. Objective: The purpose of the present study was to determine the patterns of clinical characteristics of confirmed COVID 19 patients in Sylhet to contribute as information resource of our country. Methodology: This cross sectional study was conducted in the inpatient Department of Medicine of Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, Bangladesh to evaluate the clinical characteristics among the COVID 19 patients from July 2020 to December 2020 by purposive sampling technique. For the purpose a total 75 RT PCR positive COVID 19 patients were included in the study and data were collected with a semi-structured questionnaire. Results: The results showed that,85.3%% patients presented with fever, 46.7% with cough and 38.7.0% with dyspnoea. On examination 85.3% had fever, 38.7% had tacypnea, 38.7% had low SpO2 at room temperature, 57.3% had vesicular breath sound. Lab investigations (biochemical) mostly needed at admission for management of the patients were complete blood count (CBC) in 93.3% case, c reactive protein (CRP) in 76.0% case, D-dimer in 68.0% case, random blood sugar (RBS) in 56.0% case, serum creatinine in 54.7%, serum ferritin in 42.7%, serum electrolytes in 42.7%, electro cardiogram (ECG) in 38.7%. According to clinical classification for case management of COVID 19 58.7%, 21.3%, 16%, 2.7%, 1.3% were successively diagnosed as mild, moderate, severe, asymptomatic and critical COVID 19 infection. Among the study population 80.0% patient was in need of antibiotic, 60.0% anti coagulant, 48.0% steroid, 38.7% oxygen, 2.7% antiviral drugs, 1.3% mechanical ventilation during their treatment. Conclusion: The results obtained from this study could urge more study on it to provide updated knowledge as well as find potential treatment strategies for this pandemic disease. Bangladesh Journal of Infectious Diseases, June 2024;11(1):45-51